Analisis Kinerja Karyawan PT.Sumatera Inti Karet - Valencia, Vania; Purba, Purnama Yanti; Chery, Chery; Nababan, Yudha Hotfriendi; Herawati, Novi Rachma (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The purpose of this study is to find out how work rotation, organizational communication, and work discipline impact the performance of PT workers. Sumatra Rubber Core. The background of this study is the phenomenon, namely employee discomfort with work rotation, lack of communication between employees, decreased employee performance, and disciplinary violations This study is descriptive in character and employs quantitative descriptive methodologies. Multiple linear regression was employed for data analysis, and 45 people made up the saturated sample. The research findings indicate that PT personnel' performance is unaffected by job rotation. According to Sumatra Inti Karet, work discipline does not affect employee performance concurrently with organizational communication, which has a favorable and significant impact on employee performance. In addition, organizational communication, work rotation, and work discipline have no bearing on PT employees' performance. Karet Sumatera Inti. Work rotation, organizational communication, and work discipline account for 6.9% of employee performance, according to the Adjusted R Square coefficient of determination of 0.069. Other variables not included in the study account for 93.1% of the variance in employee performance.